Visual Outcome of Open Globe Injuries in Paediatric Patients - Ambreen Gul , Ali Raza , Ambreen Gul , Ali Raza (Journal of Rawalpindi Medical College, 2018)
Background: To determine visual outcome of open globe injuries in children. Methods: In this descriptive study children, between 4-16 years (n=80), who had open globe injury and who presented within one week of injury, were included . All patients underwent surgical repair surgery. Corrected post-operative visual acuity at 4 weeks was recorded. Effect modifiers like age, gender, mechanism of injury and time delay in presentation was controlled by stratification. For post stratification chi square was applied. p-value of ≤ 0.05 accepted as statistically significant. Results: Visual improvement was observed in 70% (n=56) of patients as per operational definition, which was significantly higher in patients who presented before 24 hours (p<0.05). No other significant association was found. Conclusions: Open globe injuries require emergency surgery as a standard of care. Visual improvement was observed in 70% in this study which was significantly associated with earlier presentation (<24 hours)